Caner Bakir y Darryl S.L. Jarvis (eds.), Institutional Entrepreneurship and Policy Change: Theoretical and Empirical Explorations, Cham, Palgrave Macmillan, 2018, 314 pp. - Rodrigues de Caires, Carlos Miguel (Gestión y Política Pública, 2020)
Reseña de Carlos Miguel Rodrigues de Caires para el libro “Institutional Entrepreneurship and Policy Change: Theoretical and Empirical Explorations” de Caner Bakir y Darryl S.L. Jarvis (eds.).